Childhood traumas and psychological flexibility in patients diagnosed with generalized anxiety disorder (Annals of Medical Research, 2024)
Aim: We aimed to investigate the relationship between anxiety level, childhood trauma and psychological flexibility in patients with Generalized Anxiety Disorder (GAD).Materials and Methods:  This cross-sectional study was conducted with 100 outpatients diagnosed with generalized anxiety disorder between June 2022 and September 2022. Assessment tools were Childhood Trauma Questionnaire (CTQ), Psychological Flexibility Scale (PFS), Beck Anxiety Inventory (BAI).Results: A total of 62% of the participants in this study were women. Their average age was 36.29 ± 13.21. The regression coefficient (correlation) between CTQ and BAI is not statistically significant (p>0.05). There was a negative relationship between CTQ and PFS (r = -0.213). It was determined that when CTQ increased by one unit, the PFS value would change by β=-0.215 units. There was a negative, relationship (r = -0.372) between PFS and BAI. It was found that when PFS increases by one unit, the BAI value will change by β=-0.240 units.Conclusion: Although childhood traumas are not associated with anxiety severity in GAD patients, they may have a negative impact on psychological resilience. As psychological flexibility increases, anxiety severity decreases.
Keywords: Anxiety; Psychological flexibility; Childhood trauma; Resilience